Exploring the core microbiota in scented rice (Oryza sativa L.) rhizosphere through metagenomics approach - Dhondge, V. Harshal; Barvkar, Vitthal T.; Paul, Dhiraj; Dastager, Syed G.; Pable, Anupama A.; Nadaf, Altafhusain B. (Microbiological Research, 2022)
Rice is a major food crop cultivated around the globe. Specially scented rice varieties are of commercial importance but they are low-yielding. The rhizospheric microflora plays a significant role in improving yield and aroma. However, the core microbiome of the scented rice rhizosphere is comparatively less explored. Here, we analyzed the core microbiome associated with the rhizosphere of the scented (Ambemohar-157 and Dehradun basmati) in comparison with non-scented rice (Kolam and Arize 6444 Gold) cultivated at two different geoclimatic zones of India (Maharashtra and Uttarakhand) using the metagenomics approach. The alpha and beta diversity analysis showed that the microbial communities associated with scented and non-scented varieties significantly changes with respect to richness, diversity, and evenness. The taxonomic profiling revealed the variation in composition, diversity, and abundance of the microbiome in terms of phyla and genera associated with scented rice varieties over non-scented. The cluster analysis distinguishes the microbial communities based on their geographical positions. The core microbiome analysis revealed that scented rice rhizosphere shelters distinct and unique microbiota. 28.6 % of genera were exclusively present only in the scented rice rhizosphere. The putative functional gene annotation revealed the high abundance of genes related to the biosynthesis of 2-acetyl-1-pyrroline (2AP) precursors in scented rice. The precursor feeding analysis revealed proline as a preferred substrate by 2AP synthesizing bacteria. The 2AP precursor proline and proline metabolism genes showed a positive correlation. The scented rice-specific rhizobacteria pointed out in this study can be used as bioinoculants for enhancing aroma, yield, and sustainable rice cultivation.
Keywords: Metagenome; Microbial community; Microbiome; Oryza sativa; Rhizosphere; rice